Factors Influencing Non-compliance Behaviour of Unauthorised Drivers on Bus Rapid Transit Lanes in Lagos Metropolis - Malomo, Bolajoko I. (Advances in Social Sciences Research Journal, 2020)
The bus rapid transit lanes in Lagos are threatened by drivers of unauthorised vehicles. These vehicles could break down or be involved in a crash thereby causing delay and frustrating the major objective of constructing special lanes for the smooth operation of the bus rapid transit scheme. This study therefore employed observation method by carrying out a physical count of drivers exhibiting non-compliance behaviour on the bus rapid transit lanes for the purpose of identifying the categories of drivers that exhibit non-compliance behaviour on the lanes, and the factors responsible for their behaviour. The observation was carried out on four working days of the week, and two factors were predicted to motivate the behaviours of the drivers; traffic congestion and day of the week. In all, 652 drivers of different categories of vehicles were observed. Four hypotheses were tested using t-test and One-Way ANOVA statistics to analyse obtained data. The results revealed that drivers of private vehicles exhibited higher non-compliance behaviour compared to other categories of drivers. Additionally, traffic was a factor for non-compliance behaviour but days of the week was not a significant influence. The results are crucial for enforcement strategies, for change in policy formulation and for installation of road furniture to inform and deter unauthorized use of the bus rapid transit lanes.